VIDEO EDUKASI STOP KEKERASAN TERHADAP ANAK SEBAGAI MEDIA INFORMASI PADA DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK - Wandanaya, Anita Bawaiqki; Desrianti, Dewi Immaniar; Yuliana, Lifia (Universal Raharja Community (URNITY Journal), 2022)
ABSTRACT Almost every time there is violence against children, be it in the family, community, or school environment. Lack of information about violence against children is one of the causes of violence against children. Currently, the delivery of information by the Office of Women's Empowerment and Child Protection in Tangerang City about violence against children is only through socialization and articles on the website, so that messages about violence against children are lacking. This study aims to assist the Office of Women's Empowerment and Child Protection in Tangerang City in conveying information about violence against children through educational videos with animations. The benefit of this research is that the public can better know and understand information about violence against children, so that with this video it can reduce the number of violence against children. The research methods are: Data Collection, SWOT Analysis for writing, and Media Design and Media Production Concepts (KPM), namely: preproduction, production, and post-production. The results of the research are in the form of educational videos to stop violence in children with animations that can help the Office of Women's Empowerment and Child Protection in disseminating information about stopping violence against children so that people realize that violence against children needs to be prevented and eliminated. Keywords : Video Education, Information, Violence in Children, Tangerang City.